The Influence of the Problem-Based Learning Model on the Science Learning Motivation of Class IV Students at SDN Inpres 1 Birobuli - Ni Made Riawati; Azizah; Sri Wahyuni; Yusdin Bin M. Gagaramusu (LPPM Universitas Tadulako, 2022)
This research aims to determine the effect of the problem-based learning model on the science learning motivation of class IV students at SDN Inpres 1 Birobuli. The type of research used is quantitative research using an experimental method approach. The design of this research is quasi-experimental. The form of design used in this research is a non-equivalent control group design which consists of an experimental group and a control group. The sample in this study was class IV students at SDN Inpres 1 Birobuli, totaling 52 people, class IV A as the control class, totaling 26 students, and class IV B as the experimental class, totaling 26 students. The instrument used is a questionnaire used to measure motivation to learn science which has been tested for validity and reliability. Data analysis uses prerequisite tests, namely the normality test and homogeneity test as well as hypothesis testing using the Independent Sample t-test which is analyzed with the help of the IBM SPSS Statistics 25 program. Based on the research results, it shows a significance value (2-tailed) of 0.000 < alpha value 0.05. Because of the sign value. 0.000 < 0.05 then accepts the Ha hypothesis and rejects Ho. So it can be concluded that there is an influence of the problem-based learning model on the science learning motivation of class IV students at SDN Inpres 1 Birobuli.